Shared Services Within the Context of International Human Resource Management - Wenderoth, Martin (Prabandhan: Indian Journal of Management, 2011)
This paper evaluates the shared service concept and the ways in which it influences international human resource management (IHRM). In order to do so, the shared service concept, as well as IHRM is defined. The paper highlights the drivers and enables of shared services under consideration of the human resource (HR) function. The different application areas of the shared services concept are discussed from different angles, such as the activities that have to be performed, the type of organisations which predominantly apply the concept, as well as linked to the latter, the geographic regions where the shared services are established. Argumentation will be based on a variety of empirical studies. Finally, based on the so-called "Ulrich Model", a blueprint for a possible future HR organisation is developed. In the first instance, this paper is addressed to the scientific society as it should contribute to the comprehensive analysis of the shared service concept under special consideration of the HR function. Furthermore, the paper is addressed to practitioners searching for ways to improve the efficiency and effectiveness of their HR function, or considering the implementation of HR shared services. The moderate reader should recognise that this paper does not provide primary empirical evidence, as it is basically aimed to review the topic and provoke debate on the issues presented and discussed.